Correlation between longitudinal strain analysis and coronary microvascular dysfunction in patients with heart failure with preserved ejection fraction. (14th January 2020) - Sucato, Vincenzo; Galassi, Alfredo Ruggero; Novo, Salvatore; Saladino, Antonino; Evola, Salvatore; Novo, Giuseppina
Abstract: Objective: The aim of this study was to evaluate in patients with microvascular angina and heart failure with preserved ejection fraction, the speckle‐tracking echocardiography, and longitudinal myocardial strain to evaluate the possible presence of alterations in heart failure with preserved ejection fraction patients compared with a control population. We also investigated the correlation between the longitudinal strain analysis and the TIMI frame count after coronary angiography. Methods: Our study was performed on a population 41 patients with microvascular angina that underwent coronary angiography and speckle‐tracking echocardiography. We divided the sample into two categories: patients with heart failure with preserved ejection fraction (n‐21) and patients without heart failure with preserved ejection fraction (n‐20). We calculated TIMI frame count indices for each patient based on angiographic images. Results: Patients with heart failure with preserved ejection fraction had reduced global longitudinal strain values (−17.88) compared with the total control population, and this reduction was statistically significant ( P = .028). This reduction was more marked in patients who had a significantly increased TIMI frame count. Therefore, a statistically significant correlation was observed between TIMI frame count and global longitudinal strain. Conclusion: Our results show that cardiac contractile mechanics are altered in patients with heart failure with preserved ejection fraction at a subclinical level hard to identifiable with conventional echocardiography. The dysfunction of the microcirculation and the consequent alteration of the TIMI frame count probably results in a reduction of myocardial performance.